Respuesta :

Answer:

4

Step-by-step explanation:

I am assuming you mean (-2)^2 and not -(2)^2, correct.

If i m wrong in the assumption and its the latter one, then it is -4 since you are taking the - of 4

gmany

Answer:

-4

Step-by-step explanation:

[tex]-2^2=-4\ \text{because}\ -2^2=-(2\cdot2)=-4\\\\(-2)^2=4\ \text{because}\ (-2)^2=(-2)(-2)=4[/tex]

The parentheses are very important here.

The same in

[tex]\dfrac{2}{3}^2=\dfrac{4}{3}\\\\\left(\dfrac{2}{3}\right)^2=\dfrac{4}{9}[/tex]

ACCESS MORE